Kegiatan Corporate Social Responsibility dan Prospek Kinerja Keuangan Perusahaan Sumber Daya Alam di Indonesia, Singapura, dan Malaysia - Janita Suryani Muliate; Silvi Suhendro; Rinaningsih Rinaningsih; Vania Pradipta Gunawan (Jurnal Akuntansi)
This research aims to determine the influence of implementation and reporting of Corporate Social Responsibility (CSR) activities towards the prospect of corporate financial performance. The samples used in this research is the company of the natural resources sector operating in Indonesia, Singapore, and Malaysia from 2011 to 2017 with total samples of 25 companies and 96 observations. The data obtained is processed using quantitative research method. In this research, it is known that there are several results explaining the relationship between implementation and reporting of CSR activities to the company's financial performance in the future which is proscribed with return on asset, return on equity, cash flow from operating activities, and Tobin’s Q. The results of the study also showed significant negative results between the reporting and the implementation of CSR activities with the company's financial performance in the future. This results showed that CSR activities in Indonesia, Singapore, and Malaysia were a charity activity or just to fulfil governance’s rules.